Halogen modified ultra-microporous carbon material, preparation method and application thereof
Through the preparation of halogen-modified ultramicroporous carbon materials, the problem of difficulty in taking into account both adsorption capacity and selectivity in the prior art is solved, and efficient gas adsorption and separation is achieved, suitable for industrial applications, and energy consumption and environmental pollution are reduced.
Patent Information
- Application Number
- CN202411434589.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-17
AI Technical Summary
It is difficult to have both adsorption capacity and selectivity under low pressure conditions, and the preparation process has high energy consumption or the use of chemical solvents is unfriendly to the environment, which affects industrial applications.
The preparation method of halogen-modified ultramicroporous carbon material is used to grind and high-temperature carbonization treatment by grinding and high-temperature carbonization under a drying inert atmosphere. Enrich the pore structure and ultra-microporous carbon materials with high specific surface area to achieve efficient adsorption and separation of gas.
Ultramicroporous carbon materials with large adsorption capacity, high separation selectivity and stable physical and chemical structure were obtained. They are suitable for industrial applications, have low energy consumption and are environmentally friendly, and they show significant gas adsorption effects in low-pressure areas.
Smart Images

Figure CN119320133A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of greenhouse gas emission reduction materials, and in particular to a halogen-modified ultra-microporous carbon material for capturing CO2, CH4 and selectively separating gases, a preparation method and use thereof. Background Art
[0002] CO2 is the main greenhouse gas, and its large-scale emission brings about a series of environmental problems such as global warming and ocean acidification. How to reduce CO2 emissions has become a major challenge facing all mankind. my country is the world's largest carbon emitter, accounting for about 30% of the world's carbon emissions. Among them, flue gas emissions from thermal power plants, steel and cement industries are the main sources of carbon emissions in my country, accounting for 40% of the country's CO2 emissions. CO2 capture technology is an important means to achieve large-scale reduction of CO2 emissions in industrial flue gas, and is of great significance for responding to global climate change and achieving the "dual carbon" goals. Compared with other capture methods, physical adsorption has the advantages of strong applicability, controllable cost, simple process, environmental friendliness, and low energy consumption, but there are technical difficulties such as slow adsorption rate of CO2 by physical adsorption materials and low separation efficiency. Therefore, the development of high-performance adsorption materials is the key to capturing CO2 by physical adsorption.
[0003] Patent CN116920793A discloses a method for preparing a graphene porous material, which has a stable structure, uniform pores, and high bending strength, but has a small adsorption capacity under low pressure. Patent CN117125711A discloses a method for preparing a porous carbon material using cesium formate as an activator. The prepared porous carbon material has a high specific surface area and exhibits high CO2 adsorption activity and capture performance, but the process requires high energy consumption, which is not conducive to industrial application. Patent CN110813242A discloses a solid amine adsorbent material, which has a high CO2 adsorption capacity, but the use of amine solvents in the preparation process will cause environmental pollution. Patent CN117619350A discloses a method for preparing an activated carbon-molecular sieve composite material, which has a simple synthesis process, but the CO2 adsorption capacity is not high, and the molecular sieve is hydrophilic, and the moisture in the flue gas will compete with CO2 for adsorption, reducing the adsorption performance.
[0004] In summary, the existing physical adsorption materials have the disadvantages of high energy consumption in the preparation process or the need for chemical solvents in the preparation process, which is not environmentally friendly; it is difficult to achieve both adsorption capacity and selectivity under low pressure conditions, and flue gas impurities (water vapor, NO X ) will affect the adsorption performance of the material and many other problems. Therefore, it is crucial to develop an adsorption material with stable physicochemical structure, large gas adsorption capacity, high separation selectivity, low production energy consumption, and suitable for industrial application for greenhouse gas capture and separation. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a halogen-modified ultramicroporous carbon material with large adsorption capacity, rich pore structure, stable physicochemical structure and adjustable pore size. The ultramicroporous carbon material can be applied to the industrial field of small kinetic diameter gas capture and separation, such as adsorbing and separating CO2 from power plant flue gas, purifying and separating CH4 from mine exhaust gas, etc. The present invention now illustrates the application of CO2 adsorption and separation in power plant flue gas.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] One aspect of the present invention discloses a method for preparing a halogen-modified ultra-microporous carbon material, comprising the following steps: S1, grinding and mixing a mixture of terephthalonitrile or a halogen derivative of terephthalonitrile and anhydrous zinc chloride in a dry inert sealed atmosphere to obtain a preliminary mixture; wherein the terephthalonitrile or the halogen derivative of terephthalonitrile and the anhydrous zinc chloride are mixed in a molar mass ratio of 1:1-1.2, and the halogen derivative of terephthalonitrile is selected from at least one of tetrafluoroterephthalonitrile, tetrachloroterephthalonitrile or tetrabromoterephthalonitrile; S2, transferring the preliminary mixture to a heating container in an inert sealed atmosphere, evacuating and sealing the heating container containing the preliminary mixture, and then Then, the temperature is raised to the carbonization reaction temperature and the carbonization reaction time is maintained to perform high-temperature heating carbonization treatment; wherein the carbonization reaction temperature is 300-600°C and the carbonization reaction time is 35-45 hours; S3, after the heating container is cooled to room temperature, the crude reaction product in the heating container is taken out and ground again to obtain a post-reaction ground mixture; S4, the post-reaction ground mixture is poured into a dilute hydrochloric acid solution, stirred and washed for 20-30 hours to remove excess zinc chloride; the product obtained after stirring with the dilute hydrochloric acid solution is subsequently washed and filtered with deionized water and ethanol, and then vacuum activated at 100-150°C for 10-15 hours to obtain a final crystalline ultra-microporous carbon material.
[0008] The preparation method of the halogen-modified ultra-microporous carbon material in the above scheme replaces the hydrogen bonds of the benzene ring with halogen, and under the dehalogenation and cross-linking reaction, the material produces a rich pore structure, maintains the high specific surface area characteristics of the material, and enhances the adsorption performance; and the modification of the halogen element improves the polarity of the material, increases the surface adsorption active sites, and realizes the coupling effect between the pore structure of the microporous material and the surface polarity. Under relatively mild working conditions, the adsorption capacity of the adsorption material for gas is greatly improved, thereby efficiently adsorbing and separating carbon dioxide.
[0009] In addition, halogen atoms and higher nitrogen structures are introduced into the skeleton of the ultra-microporous carbon material by adding halogen derivatives of terephthalonitrile. Under the conditions of anhydrous zinc chloride catalysis and high-temperature carbonization, the halogen derivatives undergo dehalogenation and cross-linking reactions to achieve nitrogen doping. The nitrogen doping makes the surface of the ultra-microporous carbon material more polarized, which is beneficial to improving the adsorption performance.
[0010] The pore structures formed by the cross-linking reaction between different halogen derivatives of terephthalonitrile and anhydrous zinc chloride are different. Therefore, by adjusting the type of halogen derivatives of terephthalonitrile, the pore size of the ultra-microporous carbon material prepared for gas adsorption and separation can be changed. During the high-temperature carbonization process, the halogen derivatives of terephthalonitrile are dehalogenated to produce C=C double bonds and self-polymerize, so that the ultra-microporous carbon material forms a rich pore structure, thereby increasing the specific surface area of the material.
[0011] In the presence of anhydrous zinc chloride, halogen derivatives of terephthalonitrile undergo salt melt polycondensation to form covalent triazine-based frameworks (CTFs), in which the role of anhydrous zinc chloride is to act as a Lewis catalyst and solvent. On the one hand, it acts as a solvent in a molten state at a high temperature of 300 to 600°C; on the other hand, under the catalysis of anhydrous zinc chloride, the nitrile group undergoes trimerization to form a triazine-based polymer, accelerating the polymerization reaction.
[0012] The present invention prepares an ultra-microporous carbon material by mixing terephthalonitrile or a halogen derivative of terephthalonitrile with anhydrous zinc chloride in a molar mass ratio of 1:1 to 1.2, and the ultra-microporous carbon material has a good crystal structure and a high specific surface area, and the gas adsorption performance is improved; and the drying, oxygen-free, vacuum and other processes in the mixture grinding and synthesis engineering are emphasized, so the preparation process is simple and the energy consumption is low; and at the same time, there is no need to use an activator, a detergent and the like to carry out a process that pollutes the environment, and the ultra-microporous carbon material is environmentally friendly.
[0013] In the present invention, the molar mass ratio of terephthalonitrile or a halogen derivative of terephthalonitrile to anhydrous zinc chloride is preferably 1:1. Adding anhydrous zinc chloride in an amount equal to the reaction monomer is a prerequisite for obtaining good crystallinity, high specific surface area and pore size stratification performance, wherein 1:1 is the molar mass ratio under an ideal state, and the reaction is complete at this time; at the same time, considering the residue of the actual reaction, the molar mass can be adjusted to 1:1.2, and an appropriate amount of anhydrous zinc chloride is added to react completely with the reaction monomer, thereby improving the conversion efficiency of the reaction monomer, and then improving the crystallinity and pore size stratification of the material.
[0014] In step S1, the mixture is ground in a dry inert sealed atmosphere to avoid agglomeration, uneven mixing and other problems during the grinding process, and to eliminate the influence of moisture in the air on the crystallization and polymerization of the polymer.
[0015] In the preparation method of the halogen-modified ultra-microporous carbon material disclosed in the present invention, the carbonization reaction temperature is set to 500° C. and the carbonization reaction time is 40 hours. Based on the setting of the carbonization reaction temperature, the carbon material finally obtained can have very good crystallinity.
[0016] In the method for preparing the halogen-modified ultra-microporous carbon material disclosed in the present invention, the inert sealed atmosphere is an inert nitrogen atmosphere, and in step S2, the gas flow rate of the inert nitrogen is 50 to 500 mL / min.
[0017] In the method for preparing the halogen-modified ultra-microporous carbon material disclosed in the present invention, in step S2, the carbonization temperature rise rate is 1-10°C / min.
[0018] In the preparation method of the halogen-modified ultra-microporous carbon material disclosed in the present invention, in step S4, the ground mixture after the reaction is poured into a 2% dilute hydrochloric acid solution, stirred and washed for 24 hours to remove excess zinc chloride; then the product obtained after stirring with the dilute hydrochloric acid solution is washed and filtered with deionized water and ethanol, and then vacuum activated at 120°C for 12 hours to obtain the final crystalline ultra-microporous carbon material.
[0019] Another aspect of the present invention discloses a halogen-modified ultra-microporous carbon material for gas adsorption separation. The halogen-modified ultra-microporous carbon material is prepared by the preparation method of the halogen-modified ultra-microporous carbon material disclosed above.
[0020] In the halogen-modified ultra-microporous carbon material disclosed in the present invention, the halogen-modified ultra-microporous carbon material has a nitrogen-rich structure, a nitrogen content of 10 to 20 wt%, an average pore diameter of 0.4 to 2.1 nanometers, a pore structure of ultra-micropores and micropores, and a specific surface area of 600 to 1300 m 2 / g. In addition, the halogen-modified ultra-microporous carbon material also has a C=N structure, a carbon content of 60-80wt%, a nitrogen content of 12-15wt%, an average pore size of 0.4-0.6 nanometers, micropores with a pore size of less than 2 nanometers account for 98%-99%, ultra-micropores with a pore size of less than 0.7 nanometers account for 60%-90%, and a specific surface area of 650-1200m 2 / g.
[0021] Since carbon dioxide gas has stable chemical properties and high thermal stability, it is not easy to form chemical adsorption by electron transfer with the adsorbent surface. Therefore, constructing a pore structure and polar surface that is more inclined to match the size of adsorbed carbon dioxide molecules and enhancing the physical adsorption of the adsorbent surface and carbon dioxide molecules is an effective means to improve the carbon dioxide adsorption capacity and separation selectivity. Specific halogen-containing derivatives (F, Cl, Br, etc.) will undergo in-situ dehalogenation reactions under high temperature conditions. The removal of halogens will form carbon-carbon (C=C) double bonds inside the derivatives, thereby generating polymer microporous carbon materials with high specific surface area; and in the process of halogen dehalogenation at high temperature, ultra-microporous structures similar to the size of carbon dioxide molecules (about 0.33 nanometers) can be generated in the carbon material, which is beneficial to improve the adsorption performance of carbon dioxide, especially in the low pressure region (<P0), enhancing the affinity and adsorption potential of the adsorbent material for carbon dioxide.
[0022] In COF materials, the C=C and CN skeletons of CTFs make them exhibit good adsorption performance, and the addition of halogen elements leads to smaller pore sizes, preferably (<0.5 nanometers). Among them, the trimerization and defluorination carbonization process of fluorinated derivatives at high temperatures leads to a large loss of fluorine and carbon, producing nitrogen-rich materials; and the electrode functional groups of chloride ions can further enhance the electrostatic interaction between CTFs and CO2, and enhance the CO2 / N2 separation ability through kinetic selectivity. The synergistic effect of polar CF, C-Cl bonds and CO2-philic nitrogen-rich sites gives the framework good CO2 adsorption capacity.
[0023] Another aspect of the present invention also discloses an application of a halogen-modified ultra-microporous carbon material in gas adsorption and selective separation, preferably, in the adsorption and selective separation of CO2 in flue gas from industrial power plants and / or the adsorption and purification separation of CH4 in mine exhaust gas, wherein the test pressure is 0 to 0.1 bar and the temperature is 0 to 25°C.
[0024] In the application disclosed in the present invention, the ultra-microporous carbon material needs to be activated before application, wherein the activation temperature is 100-120°C, the activation pressure is 0.1MPa, the activation heating rate is 2-10°C / min, the activation time is 1-5h, the activation atmosphere is nitrogen, and the gas flow rate is 10-50mL / min.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The preparation method of the halogen-modified ultra-microporous carbon material of the present invention replaces the hydrogen bonds of the benzene ring with halogen. Under the dehalogenation cross-linking reaction, the obtained material has an ultra-microporous structure with better gas affinity, rich pore structure and high specific surface area, and more importantly, a crystalline structure not shown in the prior art is obtained. Compared with traditional commercial physical adsorption materials, it shows excellent gas adsorption and selective separation performance; secondly, by controlling the ratio of terephthalonitrile or halogen derivatives of terephthalonitrile and anhydrous zinc chloride, emphasizing the drying, oxygen-free, vacuum and other processes in the mixture grinding and synthesis engineering, the ultra-microporous carbon material with a certain crystalline structure and layered structure is innovatively synthesized. structure; at the same time, the preparation process is simple, the energy consumption is low, and there is no need to use activators, detergents and other environmentally polluting processes; finally, the material of the present invention has mild adsorption conditions and can efficiently adsorb gases, especially the adsorption effect is more obvious in low-pressure areas, and can be efficiently applied to the capture, separation and recovery of greenhouse gas CO2 in industrial flue gas; for methane gas with similar properties, the material can also be used for the separation and purification of CH4 in mine exhaust gas; and the material can be regenerated after desorption treatment to obtain regenerated ultra-microporous carbon material, which is easy to regenerate as an adsorbent and can be reused, has the advantages of low raw material cost, environmental friendliness, green environmental protection, etc., and is suitable for industrial production.
[0027] The halogen-modified ultramicroporous carbon material and the preparation method thereof of the present invention are disclosed in detail below in conjunction with the embodiments shown in the accompanying drawings and the reference numerals. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a flow chart of the preparation method of the halogen-modified ultra-microporous carbon material of the present invention;
[0029] Figure 2 This is a flow chart of the physical synthesis of the halogen-modified ultra-microporous carbon material obtained in the present invention;
[0030] Figure 3 The XRD curves of the halogen-modified ultra-microporous carbon materials obtained in Examples 1 and 2 of the present invention;
[0031] Figure 4 The SEM scanning electron microscope images of the halogen-modified ultra-microporous carbon materials obtained in Examples 1 and 2 of the present invention;
[0032] Figure 5 The CO2 adsorption isotherms of the halogen-modified ultra-microporous carbon materials obtained in Examples 1 and 4 of the present invention at 0°C;
[0033] Figure 6 is the N2 adsorption isotherm of the halogen-modified ultra-microporous carbon material obtained in Example 1 of the present invention at 0°C;
[0034] Figure 7The pore size distribution diagram of the halogen-modified ultra-microporous carbon material obtained in Example 1 and Example 4 of the present invention;
[0035] Figure 8 is the dynamic gas IAST separation coefficient of the halogen-modified ultra-microporous carbon material obtained in Example 1 and Example 2 of the present invention;
[0036] Fig. 9 2 is the CO2 adsorption capacity curve of the halogen ultramicroporous carbon material obtained in Examples 1 to 6 of the present invention at 0°C. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other without conflict.
[0038] like Figure 1 As shown, an embodiment of the present invention relates to a method for preparing a halogen-modified ultra-microporous carbon material, comprising the following steps: S1, grinding and mixing a mixture of terephthalonitrile or a halogen derivative of terephthalonitrile and anhydrous zinc chloride in a dry inert sealed atmosphere to obtain a preliminary mixture; wherein terephthalonitrile or a halogen derivative of terephthalonitrile and anhydrous zinc chloride are mixed in a molar mass ratio of 1:1 to 1.2, and the halogen derivative of terephthalonitrile is selected from at least one of tetrafluoroterephthalonitrile, tetrachloroterephthalonitrile or tetrabromoterephthalonitrile; S2, transferring the preliminary mixture to a heating container in an inert sealed atmosphere, evacuating and sealing the heating container containing the preliminary mixture, and then Then, the temperature is raised to the carbonization reaction temperature and the carbonization reaction time is maintained to perform high-temperature heating carbonization treatment; wherein the carbonization reaction temperature is 300-600°C and the carbonization reaction time is 35-45 hours; S3, after the heating container is cooled to room temperature, the crude reaction product in the heating container is taken out and ground again to obtain a post-reaction ground mixture; S4, the post-reaction ground mixture is poured into a dilute hydrochloric acid solution, stirred and washed for 20-30 hours to remove excess zinc chloride; the product obtained after stirring with the dilute hydrochloric acid solution is subsequently washed and filtered with deionized water and ethanol, and then vacuum activated at 100-150°C for 10-15 hours to obtain a final crystalline ultra-microporous carbon material.
[0039] In a preferred embodiment, in order to make the synthesized ultra-microporous carbon material have a better crystal structure and a high specific surface area and improve the gas adsorption performance, in step S1, terephthalonitrile or a halogen derivative of terephthalonitrile and anhydrous zinc chloride are mixed in an equal ratio of 1:1 according to the molar mass.
[0040] In the present invention, adding anhydrous zinc chloride in an amount equal to the reaction monomer is a prerequisite for obtaining good crystallinity, high specific surface area and pore size stratification performance, wherein 1:1 is the molar mass ratio under an ideal state, and the reaction is complete at this time; in actual situations, if there is any residual reaction monomer, the molar mass can be adjusted to 1:1.2 at this time, and an appropriate amount of anhydrous zinc chloride is added to react completely with the reaction monomer, thereby improving the conversion efficiency of the reaction monomer, and then improving the crystallinity and pore size stratification of the material.
[0041] In a specific embodiment, in step S2, the preliminary mixture is transferred to an ampoule bottle under an inert nitrogen sealed atmosphere, wherein the gas flow rate of the inert nitrogen gas is controlled at 50-500 mL / min, and the ampoule bottle is evacuated and sealed using a vacuum pump, and then transferred to a muffle furnace, and the carbonization heating program is set by the muffle furnace intelligent temperature control system. Specifically, the heating rate is set to 1-10°C / min, the carbonization reaction temperature is set to 500°C, and when the reaction temperature is reached, the holding time is 40 hours. Based on the setting of the carbonization reaction temperature, the carbon material finally obtained can have very good crystallinity.
[0042] In an embodiment of the present invention, in order to eliminate the influence of reaction residues on the adsorption performance of the ultra-microporous carbon material, in step S4, the post-reaction ground mixture is poured into a 2% dilute hydrochloric acid solution and stirred and washed for 24 hours, so that excess zinc chloride can be fully removed and the adsorption performance of the gas can be improved; then, the product obtained after stirring with the dilute hydrochloric acid solution is washed and filtered with deionized water and ethanol, and then vacuum activated at 120°C for 12 hours to obtain the final crystalline ultra-microporous carbon material.
[0043] The preparation method of the halogen-modified ultra-microporous carbon material provided in the embodiment of the present invention replaces the hydrogen bonds of the benzene ring with halogen. Under the dehalogenation cross-linking reaction, the obtained material has an ultra-microporous structure with better affinity for gas, rich pore structure and high specific surface area, and exhibits excellent gas adsorption and selective separation performance compared with the existing physical adsorption materials; and emphasizes the ratio of equal amounts of terephthalonitrile or halogen derivatives of terephthalonitrile and anhydrous zinc chloride, and the entire process is carried out under dry, oxygen-free and vacuum conditions, so that the synthesized ultra-microporous carbon material has high crystallinity; at the same time, the preparation process of the present invention is simple, the energy consumption is low, and there is no need to use activators, detergents, etc. to carry out environmentally polluting processes, which is environmentally friendly; and the obtained material has mild adsorption working conditions, can efficiently adsorb gas, especially the adsorption effect is more obvious in the low-pressure area, and can be efficiently used for the capture, separation and recovery of greenhouse gas CO2 in industrial flue gas; for methane gas with similar properties, the material can also be used for the separation and purification of CH4 in mine ventilation gas.
[0044] The embodiment of the present invention also provides a halogen-modified ultra-microporous carbon material for gas adsorption separation, and the halogen-modified ultra-microporous carbon material is prepared by the preparation method of the halogen-modified ultra-microporous carbon material disclosed in the above embodiment. In this embodiment, the halogen-modified ultra-microporous carbon material has a nitrogen-rich structure, a nitrogen content of 10 to 20 wt%, an average pore size of 0.4 to 2.1 nanometers, a pore structure of ultra-micropores and micropores, and a specific surface area of 600 to 1300 m 2 / g; and the halogen-modified ultra-microporous carbon material also has a C=N structure, a carbon content of 60-80wt%, a nitrogen content of 12-15wt%, an average pore size of 0.4-0.6 nanometers, micropores with a pore size of less than 2 nanometers account for 98%-99%, ultra-micropores with a pore size of less than 0.7 nanometers account for 60%-90%, and a specific surface area of 650-1200m 2 / g.
[0045] The halogen-modified ultraporous carbon material provided in the embodiment of the present invention produces an ultraporous structure similar to the size of carbon dioxide molecules (about 0.33 nanometers), and has mild adsorption conditions, can efficiently adsorb gases, especially the adsorption effect is more obvious in low-pressure areas, and can be efficiently applied to the capture, separation and recovery of greenhouse gas CO2 in industrial flue gas; for methane gas with similar properties, the material can also be used for the separation and purification of CH4 in mine exhaust gas; and the material can be regenerated after desorption treatment to obtain regenerated ultraporous carbon material, which is easy to regenerate as an adsorbent and can be reused, has the advantages of low raw material cost, environmental friendliness, green environmental protection, etc., and is suitable for industrial production.
[0046] The embodiment of the present invention also provides an application of a halogen-modified ultra-microporous carbon material in gas adsorption and selective separation, preferably, in the adsorption and selective separation of CO2 in flue gas from industrial power plants and / or the adsorption and purification separation of CH4 in mine ventilation gas. In this embodiment, the ultra-microporous carbon material needs to be activated before application, wherein the activation temperature is 100-120°C, the activation pressure is 0.1MPa, the activation heating rate is 2-10°C / min, the activation time is 1-5h, the activation atmosphere is nitrogen, and the gas flow rate is 10-50mL / min.
[0047] The calculation and analysis methods used in the embodiments of the present invention mainly include:
[0048] (1) Analysis method of element content: X-ray fluorescence spectrometry (PANalytical Axios) was used to analyze nitrogen, carbon and halogen elements;
[0049] (2) Calculation method of average pore size, pore volume and ultra-micropore ratio: The calculation results can be obtained by characterizing the carbon dioxide isotherm adsorption curve of ultra-microporous carbon materials and using the Density Functional Theory (DFT) model to simulate and calculate;
[0050] (3) Calculation method of specific surface area: The specific surface area can be obtained by characterizing the carbon dioxide isotherm adsorption curve of ultra-microporous carbon materials and using the multi-point Brunauer-Emmett-Teller (BET) model to simulate and calculate;
[0051] (4) Maximum gas adsorption capacity and gas selectivity of materials The selectivity of CO2 / N2 is calculated based on the ideal solution adsorption theory (IAST). First, the single-point Langmuir model is used to fit the experimental adsorption isotherm:
[0052]
[0053] Where: b i is the Langmuir constant (Pa -1 );p i is the volume gas phase pressure of substance i (Pa); q i is the molar loading of substance i (mmolg -1 );q i,sat is the saturation capacity of substance i (mmolg -1 ).
[0054] According to the ideal adsorption solution theory (IAST) proposed by Myers and Prausnitz, the adsorption selectivity S of a binary mixture (adsorbed solutes 1 and 2) is ads Defined as:
[0055]
[0056] The present invention calculates the binary mixed gas selectivity of adsorbed solute 1 and adsorbed solute 2 based on the graphical interface GraphIAST of PYthon, and can set the maximum partial pressure at the input end, and set the gas mole number from 0 to 1, so as to realize dynamic prediction of gas selectivity. Wherein adsorbed solute 1 is carbon dioxide, and adsorbed solute 2 is nitrogen.
[0057] Example 1
[0058] Terephthalonitrile and anhydrous zinc chloride were uniformly ground in a mass ratio of 1:1, transferred to an ampoule under an inert nitrogen atmosphere, and the ampoule was evacuated and sealed using a vacuum pump. The ampoule was then placed in a muffle furnace and heated to 400°C at a rate of 10°C / min for 40 hours. After the muffle furnace was cooled to room temperature, the crude product was taken out and carefully ground, and then poured into a 2% HCl solution and stirred for 24 hours to remove the residual zinc chloride in the reaction. Finally, it was washed with deionized water and ethanol three times, the filtered sample was centrifuged, and activated under vacuum conditions at 120°C for 12 hours to finally obtain the CTF-1 ultra-microporous carbon material, which was weighed and the final yield of the CTF-1 ultra-microporous carbon material was calculated.
[0059] In this example, the calculation method and analysis method disclosed in the above example are used to obtain the XRD curve of the CTF-1 material obtained in Example 1. The results are as follows: Figure 3 As shown in the figure, it can be clearly seen that the spectrum of the CTF-1 material has a high-intensity narrow peak at a small diffraction angle, indicating that the CTF-1 material has a certain crystal structure and the pores are a two-dimensional hexagonal structure, which is consistent with the previous research results. It can be understood by those skilled in the art that this embodiment achieves the crystallinity of the CTF-1 material by means of a simple ion thermal reaction at 400°C, presenting a two-dimensional hexagonal structure, which is significantly different from the scheme and effect of other methods in the prior art that require complex chemical reactions to change the skeleton structure.
[0060] The SEM scanning electron microscope image of the CTF-1 material obtained in Example 1 shows the following results: Figure 4 As shown in the figure, it can be clearly seen that the CTF-1 material has a certain crystalline structure, and the local microscopic agglomeration phenomenon is present. However, as the synthesis temperature increases, the agglomeration characteristics weaken, and the pore structure of the material appears to be honeycombed, indicating that the increase in synthesis temperature has opened up the pores of the material to a certain extent.
[0061] The CO2 adsorption isotherm of the CTF-1 material obtained in Example 1 at 0°C is as follows: Figure 5As shown in the figure, the trend of the CO2 adsorption isotherm can be clearly seen. The CTF-1 material exhibits the characteristics of a type I adsorption curve, and the adsorption curve has no hysteresis loop. This phenomenon indicates that the prepared CTF-1 material is a typical microporous material.
[0062] The CTF-1 material obtained in Example 1 has a nitrogen content of 12.2%, a carbon content of 83.1%, a pore size of <2 nm and a micropore size of <0.7 nm, accounting for 98% and 30%, respectively. The pore volume can reach 0.72 cm 3 / nm / g, specific surface area S BET 725m 2 / g, the adsorption capacity of carbon dioxide reaches 2.45mmol / g, and the gas selectivity coefficient is calculated based on GraphIAST. The dynamic three-dimensional graph is as follows Figure 8 As shown, at 1 bar, when the gas molar number is CO2:N2=1:9, the calculated gas selectivity coefficient IAST is 25.
[0063] Example 2
[0064] The operation of Example 2 is the same as that of Example 1, except that tetrachloroterephthalonitrile is selected as the synthetic monomer, and other operations remain unchanged. The prepared chlorinated ultramicroporous carbon material is recorded as ClCTF-1.
[0065] In this embodiment, based on the operating steps of the method provided by the present invention, under the halogen polymerization reaction, the chlorinated layered structure brought by the chlorine element causes spacing to exist in the pore structure, thereby presenting crystallinity that is not reflected in the prior art. Specifically, using the calculation method and analysis method disclosed in the above embodiment, the XRD curve of the ClCTF-1 material obtained in Example 2 is as follows: Figure 3 As shown, broad diffraction appears near a small diffraction angle of 2 to 8°, indicating that the material synthesis presents a crystalline structure. The material has a black and bright metallic luster and a hard texture. A narrow peak appears near 18°, indicating that the ClCTF-1 pore component has a layered structure. The ClCTF-1 material obtained in Example 2 has a nitrogen content of 16.1%, a carbon content of 63.8%, a micropore with a pore size of less than 2 nm, a micropore with a pore size of less than 0.7 nm, and a pore volume of up to 0.94 cm 3 / nm / g, specific surface area S BET 750m 2 / g, the adsorption capacity of carbon dioxide reaches 4.80mmol / g, and the dynamic three-dimensional diagram of gas selectivity prediction is shown in Figure 8 As shown, at 1 bar, when the gas molar number is CO2:N2=1:9, the calculated gas selectivity coefficient IAST is 26.
[0066] Example 3
[0067] The operation of Example 3 is the same as that of Example 1, except that tetrafluoroterephthalonitrile is selected as the synthetic monomer, and other operations remain unchanged. The prepared chlorinated ultramicroporous carbon material is recorded as FCTF-1.
[0068] In this embodiment, the calculation method and analysis method disclosed in the above embodiment are used. The nitrogen content of the FCTF-1 material obtained in Example 3 is 12.9%, the carbon content is 60.8%, the micropores with a pore size of less than 2 nm account for 99%, the ultramicropores with a pore size of less than 0.7 nm account for 60%, and the specific surface area S BET 660m 2 / g, pore volume can reach 0.84cm 3 / nm / g, the adsorption capacity for carbon dioxide reaches 4.61mmol / g. At 1bar, when the gas molar number is CO2:N2=1:9, the gas selectivity coefficient IAST is 33.
[0069] Example 4
[0070] The operation of Example 4 is the same as that of Example 1, except that the carbonization synthesis temperature is changed to 500° C., and other operations remain unchanged. The prepared chlorinated ultramicroporous carbon material is recorded as CTF-1-500.
[0071] In this embodiment, the calculation method and analysis method disclosed in the above embodiment are used. The nitrogen content of CTF-1-500 obtained in Example 4 is 13.1%, the carbon content is 81.3%, the micropores with a pore size of less than 2 nm account for 35%, the ultramicropores with a pore size of less than 0.7 nm account for 30%, and the pore volume can reach 0.72 cm 3 / nm / g, specific surface area S BET 1140m 2 / g, the carbon dioxide adsorption capacity is 3.14mmol / g, and at 1bar, when the gas molar number is CO2:N2=1:9, the gas selectivity coefficient IAST is 23.
[0072] Example 5
[0073] The operation of Example 5 is the same as that of Example 1, except that tetrachloroterephthalonitrile is used as the synthetic monomer, the carbonization synthesis temperature is changed to 500° C., and other operations remain unchanged. The prepared ultramicroporous carbon material is recorded as ClCTF-1-500.
[0074] In this embodiment, the calculation method and analysis method disclosed in the above embodiment are used. The nitrogen content of the ClCTF-1-500 material obtained in Example 5 is 14.5%, the carbon content is 80.5%, the micropores with a pore size of less than 2 nm account for 20%, the ultramicropores with a pore size of less than 0.7 nm account for 10%, and the pore volume can reach 1.28 cm 3 / nm / g, specific surface area S BET 1270m2 / g, the carbon dioxide adsorption capacity is 5.35mmol / g, and at 1bar, when the gas molar number is CO2:N2=1:9, the gas selectivity coefficient IAST is 24.
[0075] Example 6
[0076] The operation of Example 6 is the same as that of Example 1, except that tetrafluoroterephthalonitrile is selected as the synthetic monomer, the carbonization synthesis temperature is changed to 500° C., and other operations remain unchanged. The prepared ultramicroporous carbon material is recorded as FCTF-1-500.
[0077] In this embodiment, the calculation method and analysis method disclosed in the above embodiment are used. The nitrogen content of the FCTF-1-500 material obtained in Example 6 is 14.5%, the carbon content is 80.5%, the average pore size is 0.5 nm, the micropores with a pore size of <2 nm account for 99%, the ultramicropores with a pore size of <0.7 nm account for 90%, and the pore volume can reach 1.15 cm 3 / nm / g, specific surface area S BET 1140m 2 / g, the carbon dioxide adsorption capacity reaches 5.18mmol / g. At 1bar, when the gas molar number is CO2:N2=1:9, IAST is 24.
[0078] Secondly, the halogen-modified ultra-microporous carbon material of the present invention is subjected to the conditions of 0°C and 0 to 1 atmosphere pressure. The pressure is measured at a specific pressure value to determine the adsorption value of CO2 by the synthesized halogen-modified ultra-microporous carbon material. The CO2 adsorption capacity of the synthetic example provided is as follows: Fig. 9 shown.
[0079] Table 1 summarizes the CO2 adsorption performance evaluation results of the carbon-based materials prepared in Examples 1 to 6 under the above test conditions. It also summarizes the performance of common physical adsorption materials as comparative examples. The results show that the CO2 adsorption performance of the comparative examples is significantly lower than that of the ultramicroporous carbon materials prepared in the embodiments of the present invention.
[0080] Table 1 Evaluation results of carbon dioxide adsorption performance of various embodiments and comparative examples
[0081]
[0082]
[0083] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. The halogen-modified microporous carbon material provided by the present invention can also be applied to other gas adsorption and separation fields, such as separation and purification of CH4 from mine ventilation gas, etc. Any other modifications, modifications, composites, etc. that do not deviate from the essential principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a halogen-modified ultra-microporous carbon material, characterized in that: The steps include: S1, grinding and mixing a mixture of terephthalonitrile or a halogen derivative of terephthalonitrile and anhydrous zinc chloride in a dry inert sealed atmosphere to obtain a preliminary mixture; wherein the terephthalonitrile or the halogen derivative of terephthalonitrile and the anhydrous zinc chloride are mixed in a molar weight ratio of 1:1-1.2, and the halogen derivative of terephthalonitrile is selected from at least one of tetrafluoroterephthalonitrile, tetrachloroterephthalonitrile or tetrabromoterephthalonitrile; S2, transferring the preliminary mixture into a heating container under an inert sealed atmosphere, evacuating and sealing the heating container containing the preliminary mixture, and then heating it to a carbonization reaction temperature and maintaining the carbonization reaction time to perform a high-temperature heating carbonization treatment; wherein the carbonization reaction temperature is 300-600° C., and the carbonization reaction time is 35-45 hours; S3, after the heating container is cooled to room temperature, the crude reaction product in the heating container is taken out and ground again to obtain a post-reaction ground mixture; S4, pouring the ground mixture after the reaction into a dilute hydrochloric acid solution, stirring and washing for 20-30 hours to remove excess zinc chloride; then washing and filtering the product obtained after stirring with the dilute hydrochloric acid solution with deionized water and ethanol, and then vacuum activating at 100-150°C for 10-15 hours to obtain the final crystalline ultra-microporous carbon material.
2. The method for preparing the halogen-modified ultra-microporous carbon material according to claim 1, characterized in that: The terephthalonitrile or the halogen derivative of terephthalonitrile and anhydrous zinc chloride are mixed in equal amounts according to a molar mass ratio of 1:
1.
3. The method for preparing the halogen-modified ultra-microporous carbon material according to claim 2, characterized in that: The carbonization reaction temperature was set to 500° C., and the carbonization reaction time was 40 hours.
4. The method for preparing the halogen-modified ultra-microporous carbon material according to claim 2, characterized in that: The inert sealed atmosphere is an inert nitrogen atmosphere, and in step S2, the gas flow rate of the inert nitrogen is 50 to 500 mL / min.
5. The method for preparing the halogen-modified ultra-microporous carbon material according to claim 2, characterized in that: In step S2, the carbonization temperature rise rate is 1-10°C / min.
6. The method for preparing the halogen-modified ultra-microporous carbon material according to claim 2, characterized in that: In step S4, the post-reaction ground mixture is poured into a 2% dilute hydrochloric acid solution and stirred and washed for 24 hours to remove excess zinc chloride; the product obtained after stirring with the dilute hydrochloric acid solution is then washed and filtered with deionized water and ethanol, and then vacuum activated at 120°C for 12 hours to obtain the final crystalline ultra-microporous carbon material.
7. A halogen-modified ultra-microporous carbon material for gas adsorption separation, characterized in that: The halogen-modified ultra-microporous carbon material is prepared by the preparation method of the halogen-modified ultra-microporous carbon material according to any one of claims 1-6.
8. The halogen-modified ultra-microporous carbon material according to claim 7, characterized in that: The halogen-modified ultra-microporous carbon material has a nitrogen-rich structure, a nitrogen content of 10-20 wt%, an average pore diameter of 0.4-2.1 nanometers, a pore structure of ultra-micropores and micropores, and a specific surface area of 600-1300 m 2 / g.
9. The halogen-modified ultra-microporous carbon material prepared according to claim 8, characterized in that: The halogen-modified ultra-microporous carbon material has a C=N structure, a carbon content of 60-80 wt%, a nitrogen content of 12-15 wt%, an average pore size of 0.4-0.6 nanometers, micropores with a pore size of less than 2 nanometers account for 98%-99%, ultra-micropores with a pore size of less than 0.7 nanometers account for 60%-90%, and a specific surface area of 650-1200 m 2 / g.
10. Use of the halogen-modified ultra-microporous carbon material according to any one of claims 7 to 9 in gas adsorption and selective separation, especially in CO2 adsorption and selective separation in flue gas from industrial power plants and / or CH4 adsorption and purification separation in mine ventilation gas.
11. The use according to claim 10, characterized in that: The ultra-microporous carbon material needs to be activated before application, wherein the activation temperature is 100-120°C, the activation pressure is 0.1MPa, the activation heating rate is 2-10°C / min, the activation time is 1-5h, the activation atmosphere is nitrogen, and the gas flow rate is 10-50mL / min.
Citation Information
Patent Citations
Flue gas CO2 capturing material and production method thereof
CN110813242A
Porous carbon material as well as preparation method and application thereof
CN117125711A
Activated carbon-molecular sieve composite material capable of adsorbing CO2 and preparation method thereof
CN117619350A
Cited By
Porous carbon material as well as preparation method and application thereof
CN120987297A